Intelligent Decision Support System for Home Automation - ANFIS Based Approach - K, Reena; Venkatesh, Veeramuth (International Journal of Engineering and Technology, 2018)
Internet of Things (IoT) deals with the idea of remotely multiplexing and monitoring real-world things via Internet. This idea can be incorporated at home appliances to make it smarter, safer and automated. This design focuses on constructing a smart, wireless home security system that gives alerts to the respective user through the Internet. This paper gives a smart decision support system to various home automation services using fuzzy logic. The proposed system is built on Adaptive Neuro-Fuzzy Inference System (ANFIS). Itâ€™s a kind of artificial neural network that is used here for deciding on the changes taking place in the sensing unit. Through this simple method, various parameters such as temperature level, light intensity and human presenc eare monitored and controlled.Â